Math Problems

Get a common denominator in order to evaluate the following

## Questions

 $$\frac{1}{2} + \frac{1}{8} =$$ _______ $$\frac{6}{7} + \frac{1}{3} =$$ _______ $$\frac{2}{3} - \frac{1}{2} =$$ _______ $$\frac{3}{4} - \frac{1}{9} =$$ _______ $$\frac{1}{3} + \frac{1}{4} =$$ _______ $$\frac{4}{5} + \frac{1}{3} =$$ _______ $$\frac{3}{4} + \frac{1}{3} =$$ _______ $$\frac{3}{5} + \frac{8}{9} =$$ _______ $$\frac{6}{7} - \frac{2}{7} =$$ _______ $$\frac{1}{7} + \frac{5}{8} =$$ _______ $$\frac{2}{5} + \frac{8}{9} =$$ _______ $$\frac{1}{2} - \frac{1}{4} =$$ _______ $$\frac{3}{4} + \frac{1}{8} =$$ _______ $$\frac{1}{2} + \frac{1}{3} =$$ _______ $$\frac{1}{2} - \frac{4}{9} =$$ _______ $$\frac{5}{6} - \frac{7}{9} =$$ _______ $$\frac{7}{9} + \frac{8}{9} =$$ _______ $$\frac{5}{6} + \frac{3}{8} =$$ _______ $$\frac{2}{5} - \frac{3}{7} =$$ _______ $$\frac{1}{4} + \frac{2}{3} =$$ _______ $$\frac{1}{5} - \frac{1}{4} =$$ _______ $$\frac{2}{7} + \frac{2}{3} =$$ _______ $$\frac{1}{7} - \frac{7}{8} =$$ _______ $$\frac{1}{3} + \frac{2}{3} =$$ _______ $$\frac{1}{2} + \frac{5}{7} =$$ _______ $$\frac{1}{8} + \frac{5}{9} =$$ _______ $$\frac{1}{5} - \frac{1}{9} =$$ _______ $$\frac{2}{9} + \frac{2}{3} =$$ _______

 $$\frac{1}{2} + \frac{1}{8} = \frac{5}{8}$$ $$\frac{6}{7} + \frac{1}{3} = \frac{25}{21}$$ $$\frac{2}{3} - \frac{1}{2} = \frac{1}{6}$$ $$\frac{3}{4} - \frac{1}{9} = \frac{23}{36}$$ $$\frac{1}{3} + \frac{1}{4} = \frac{7}{12}$$ $$\frac{4}{5} + \frac{1}{3} = \frac{17}{15}$$ $$\frac{3}{4} + \frac{1}{3} = 1 \frac{1}{12}$$ $$\frac{3}{5} + \frac{8}{9} = \frac{67}{45}$$ $$\frac{6}{7} - \frac{2}{7} = \frac{4}{7}$$ $$\frac{1}{7} + \frac{5}{8} = \frac{43}{56}$$ $$\frac{2}{5} + \frac{8}{9} = 1 \frac{13}{45}$$ $$\frac{1}{2} - \frac{1}{4} = \frac{1}{4}$$ $$\frac{3}{4} + \frac{1}{8} = \frac{7}{8}$$ $$\frac{1}{2} + \frac{1}{3} = \frac{5}{6}$$ $$\frac{1}{2} - \frac{4}{9} = \frac{1}{18}$$ $$\frac{5}{6} - \frac{7}{9} = \frac{1}{18}$$ $$\frac{7}{9} + \frac{8}{9} = 1 \frac{2}{3}$$ $$\frac{5}{6} + \frac{3}{8} = \frac{29}{24}$$ $$\frac{2}{5} - \frac{3}{7} = \frac{-1}{35}$$ $$\frac{1}{4} + \frac{2}{3} = \frac{11}{12}$$ $$\frac{1}{5} - \frac{1}{4} = \frac{-1}{20}$$ $$\frac{2}{7} + \frac{2}{3} = \frac{20}{21}$$ $$\frac{1}{7} - \frac{7}{8} = \frac{-41}{56}$$ $$\frac{1}{3} + \frac{2}{3} = 1$$ $$\frac{1}{2} + \frac{5}{7} = 1 \frac{3}{14}$$ $$\frac{1}{8} + \frac{5}{9} = \frac{49}{72}$$ $$\frac{1}{5} - \frac{1}{9} = \frac{4}{45}$$ $$\frac{2}{9} + \frac{2}{3} = \frac{8}{9}$$